Pengaruh Kualitas Layanan dan Kewajaran Harga Terhadap Niat Wisatawan Domestik Menginap Kembali di Alam Kulkul Boutique Resort Kuta-Bali - Pratama, IGst Bagus Karla; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
ABSTRACT This research is classified by research of asosiatif with aim to know positive influence and signifikan from quality of service and equity of price by simultan is, positive, and compare most dominant to domestic tourist intention again lodge in Nature of Kulkul Boutique Resort Kuta-Bali. This Research is done in Alam Kulkul Boutique Resort Kuta-Bali with technique of análisis doubled linear regresi. Amount of got sampel by using method of Acindental Sampling is counted 100 responder. Pursuant to result of analysis can be found that quality of service and equity of price have an effect on by positive to domestic tourist intention again lodge in Alam Kulkul Boutique Resort Kuta-Bali with value of F test (77,069) > F table ( 3,07). quality of service and equity of price have an effect on positive and signifikan to domestic tourist intention again lodge in Alam Kulkul Boutique Resort Kuta-Bali. This can be proved from value of t test larger ones of value of t- table of. Equity of price represent most influencing variable of domestic tourist intention again lodge in Alam Kulkul Boutique Resort Kuta-Bali. Normal 0 false false false EN-US JA X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";}
Keywords: Keyword: quality of service, equity of price, and tourist intention.